Mg thermal diffusion behavior on the band modulation of MgxZn1-xO/ZnO metal-semiconductor-metal photodetectors. (15th August 2018) - Hwang, J.D.; Lin, J.S.; Hwang, S.B.
Abstract: By magnesium (Mg) atom diffusion in ZnO layer, the detection band of Mgx Zn1-x O/ZnO metal-semiconductor-metal photodetectors (MSM-PDs) could be modulated from two distinct bands to one band. ZnO and Mgx Zn1-x O layers were deposited consecutively on a sapphire substrate using an radio-frequency magnetron sputtering system. With increasing annealed temperature, Mg atoms diffuse from Mgx Zn1-x O into the underlying ZnO layer, which tunes the composition of ZnO into Mgy Zn1-y O and thus modulate the detection band of MSM-PDs. For the annealed temperature below 900 °C, two distinct bands were detected in the MSM-PDs with wavelength region of 280–330 nm and 360–400 nm due to the absorption of Mgx Zn1-x O and underlying ZnO layers. Further increasing the annealed temperature to 900 °C, the deeply diffusing Mg atom causes the Mgx Zn1-x O and ZnO layers were homogenized into a uniform Mgz Zn1-z O layer, hence the detection band was transformed into one band with a wavelength region of 280–340 nm. Secondary ion mass spectrometry depth profile showed the Mg atom diffusing downwards with increasing annealed temperature, causing the Mg content to decrease from ~ 30% in the as deposited Mgx Zn1-x O to ~ 8% in the homogenized Mgz Zn1-z O layer. Photoluminescence demonstrated the as-deposited Mgx Zn1-x O/ZnO bi-layer having two distinct emission peaks around 340 and 400 nm, and the Mgx Zn1-x O and ZnO layers were homogenized into a Mgz Zn1-z O layer in 900 °C and hence only one emission peak (355 nm).